Graduate employability concerns amidst a crisis: Student perspectives from Singapore on COVID-19. Issue 3 (June 2023) - Tan, Eunice; Mwagwabi, Florence; Lim, Tania; Lim, Amy
With the ongoing challenges of COVID-19, global economies continue to face uncertainties, widespread workforce volatility and employment challenges. During a sustained crisis such as the COVID-19 pandemic, university students' self-perceptions about their employability and future career choices in their chosen industry sectors may be affected. Therefore, this study investigates graduate employability concerns and the perceptions of undergraduate students regarding employment prospects and future job security confidence in their disciplines' industry sectors in light of this global crisis. Through the employment of a mixed methods design, the study investigates the perceptions of graduating students from three disciplines in Singapore: Tourism, Communications and Information Technology. The findings indicate that COVID-19 had a positive impact on perceptions of jobs that could be performed from home and those in essential services. Concurrently, there were notable variances in the students' perceptions regarding career prospects and job security confidence across the three disciplines with regard to the impact of the crisis on their industry sectors in general and themselves individually.